2020
DOI: 10.1002/ejoc.202000871
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Properties of Fused π‐Extended Acridone Derivatives

Abstract: Benzene‐ and naphthalene‐fused acridone derivatives with hexyl and phenyl groups at the amino position were synthesized and their properties were investigated experimentally and computationally. All the structures of these fused π‐extended acridone derivatives were unambiguously confirmed by single‐crystal X‐ray analysis, which revealed the presence of face‐to‐face π–π stackings along the acridone moiety and the intermolecular hydrogen bond‐directed molecular packings of the phenyl‐substituted acridone derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Acridone and its derivatives have very similar structures as xanthone and thioxanthone, and they have been widely applied in pharmaceutical development, new materials, and biological probes. Their fluorescence quantum yields were reported to be higher than those of xanthone and thioxanthone. , Recently, one acridone derivative ( N -methyl-difluoro-acridone), which emits blue fluorescence with a quantum yield of 0.87 in methanol, has been shown to have the ability to covert both singlet and triplet exactions into light even though no singlet–triplet equilibrium state is observed and thus it is potentially suitable as a blue OLED emitter . A previous theoretical study by Marian and Rai-Constapel suggested that equilibrium between 1 ππ* and 3 n O π* states could exist in acridone since ISC and rISC can take place on a picosecond timescale when it is in acetonitrile .…”
Section: Introductionmentioning
confidence: 99%
“…Acridone and its derivatives have very similar structures as xanthone and thioxanthone, and they have been widely applied in pharmaceutical development, new materials, and biological probes. Their fluorescence quantum yields were reported to be higher than those of xanthone and thioxanthone. , Recently, one acridone derivative ( N -methyl-difluoro-acridone), which emits blue fluorescence with a quantum yield of 0.87 in methanol, has been shown to have the ability to covert both singlet and triplet exactions into light even though no singlet–triplet equilibrium state is observed and thus it is potentially suitable as a blue OLED emitter . A previous theoretical study by Marian and Rai-Constapel suggested that equilibrium between 1 ππ* and 3 n O π* states could exist in acridone since ISC and rISC can take place on a picosecond timescale when it is in acetonitrile .…”
Section: Introductionmentioning
confidence: 99%
“…However, such method often leads to the generation of pyridone-doped aromatic system in the angular shape with weakened conjugation of benzene at the turning region. [11] To access the acenes in the linear fashion, the palladium-catalyzed Buchwald-Hartwig amination was utilized to build the pyridone unit. [12] Treatment of the dibrominated compound 1 with Turbo Grignard reagent afforded the mono-Grignard reagent, which underwent the nucleophilic addition to the ortho-brominated aldehydes to generate the alcohols 2 in 33-52 % yields.…”
Section: Resultsmentioning
confidence: 99%
“…The acid-catalyzed intramolecular cyclization of diarylamine derivatives bearing ester function represents a valuable strategy for the construction of quinolone frameworks via Friedel-Crafts-type reaction [30]. Hence, we decided to adopt this methodology for the synthesis of azuleno [2,1-b]quinolones.…”
Section: Resultsmentioning
confidence: 99%